2016
DOI: 10.1093/jme/tjw115
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown Resistance Mutations in Aedes aegypti (Diptera: Culicidae) From Puerto Rico

Abstract: Permethrin resistance is widespread in Aedes aegypti (L.), the main dengue, zika, and chikungunya virus vector in Latin America and the Caribbean. A common mechanism of resistance to pyrethroids-knockdown resistance (kdr)-is conferred through mutations in the insect's voltage-dependent sodium channel. In this mosquito, around 10 replacement substitutions in the voltage-gated sodium channel gene (vgsc) have been reported in pyrethroid-resistant strains. Two of these mutations, named Ile1,016 and Cys1,534, are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 21 publications
1
39
0
4
Order By: Relevance
“…1(a)). The overall curve fit of the EC 50 for metofluthrin decreased from 0.29 (0.13-0.66) to 0.26 (0.12-0.55) μg cm -2 against the OR strain and from 17 (10-30) to 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) against the PR strain ( Fig. 1(a)).…”
Section: Impact Of the Pabt On Calculated Response Potenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a)). The overall curve fit of the EC 50 for metofluthrin decreased from 0.29 (0.13-0.66) to 0.26 (0.12-0.55) μg cm -2 against the OR strain and from 17 (10-30) to 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) against the PR strain ( Fig. 1(a)).…”
Section: Impact Of the Pabt On Calculated Response Potenciesmentioning
confidence: 99%
“…For example, Ae. aegypti from Puerto Rico showed up to 214‐fold resistance to permethrin, and 650‐fold resistance to deltamethrin compared to the susceptible Orlando strain . The resistance mechanisms in this strain include knockdown resistance due to two kdr mutations, V1016I and F1534C, present at 0.97 and 1.00 frequencies, respectively, in the voltage‐dependent sodium channel gene, as well as upregulated cytochrome P450s and glutathione‐ S ‐transferases …”
Section: Introductionmentioning
confidence: 98%
“…Pyrethroid resistance and kdr alleles have been well documented in Ae. aegypti strains from Central America, South America and the Caribbean [7-11]. Recent testing as part of the Zika emergency response in Puerto Rico has shown that isolated, early reports of resistance were indicative of widespread resistance on the island [11-14].…”
Section: Introductionmentioning
confidence: 99%
“…aegypti strains from Central America, South America and the Caribbean [7-11]. Recent testing as part of the Zika emergency response in Puerto Rico has shown that isolated, early reports of resistance were indicative of widespread resistance on the island [11-14]. Studies have also shown the pyrethroid resistance is not specific to a particular chemical but is generally class-wide to type I, type II, and non-ester pyrethroids [11, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…The heavy reliance on permethrin-based products raised concerns, given recent reports that Ae. aegypti populations in 8 municipalities were already highly resistant to it ( 7 ). …”
mentioning
confidence: 99%